A cosmopolitan jurisprudence : essays in memory of H. Patrick Glenn / edited by Helge Dedek, McGill University. - Dedek, Helge, 1973-; Glenn, H. Patrick (ASCL studies in comparative law., 2022)
H. Patrick Glenn (1940-2014), Professor of Law and former Director of the Institute of Comparative Law at McGill University, was a key figure in the global discourse on comparative law. This collection is intended to honor Professor Glenn's intellectual legacy by engaging critically with his ideas, especially focusing on his visions of a 'cosmopolitan state' and of law conceptualized as 'tradition'. The book explores the intellectual history of comparative law as a discipline, its attempts to push the objects of its study beyond the positive law of the nation-state, and both its potential and the challenges it must confront in the face of the complex phenomena of globalization and the internationalization of law. An international group of leading scholars in comparative law, legal philosophy, legal sociology, and legal history takes stock of the field of comparative law and where it is headed.